New insight for ulcerative colitis diagnosis via serum netrin-1 and galectin-1 biomarkers - Alahmed, Atika; Al-Rubaee, Eaman (Human antibodies, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory disease of the large intestine. There are different studies about the role and the diagnostic utility of Galectin-1 (Gal-1) and Netrin-1 (Net-1) in multiple diseases such as diabetes, liver and heart diseases as well as brain and colonic cancer where they used to highlight the relationship between the inflammatory process and the disease pathogenesis. The present study aimed to evaluate their role as biomarkers for UC.MethodsThis case-control study included a total of 90 subjects where 60 UC patients including newly diagnosed and previously diagnosed cases were gathered and compared to 30 healthy controls, the sample collection done at the Gastroenterology and Hepatology Hospital in Basrah, Iraq. Serum levels of Gal-1 and Net-1 were measured via ELISA kits, and diagnostic accuracy was assessed using one-way ANOVA and Receiver Operating Characteristic (ROC) curve analysis.ResultsThe mean levels of Gal-1 and Net-1 were significantly elevated in the newly diagnosed UC group compared to the previously diagnosed group and healthy controls. ROC analysis demonstrated excellent diagnostic accuracy for both biomarkers, with area under the curve (AUC) values of 0.90 for Gal-1 and 0.96 for Net-1. Optimal cut-off points for distinguishing UC patients from healthy controls were 2.850 ng/mL for Gal-1 and 903.5 pg/mL for Net-1.ConclusionSerum Gal-1 and Net-1 exhibit high diagnostic accuracy in differentiating UC patients from healthy individuals, suggesting their potential as promising biomarkers for UC diagnosis. Further studies are needed to validate these findings and explore their clinical applicability.